INCLUSIVE HIGHER EDUCATION: SOCIO-PSYCHOLOGICAL WELL-BEING OF STUDENTS - V. Z. Kantor; Yu. L. Proekt (Образование и наука)
Introduction. Nowadays, substantial intensification of inclusive processes in educational system (especially in higher education) identifies the need for thorough research of psycho-pedagogical foundations for the development of inclusive education culture.The aim of this research was to identify and compare the levels and factors of social-psychological well-being of healthy students, students with disabilities and students of inclusive groups.Methodology and research methods. At the methodological level, the research was based on the proposition that inclusive education assumes the formation and support of such an integrative socio-psychological space, in which neither students with disabilities nor healthy students feel anxiety in the course of interaction in the classroom or out-of-class situation. As the main methodological tool,a specially designed questionnaire was used for fixing the socio-emographic characteristics of the respondents, as well as for clarifying the problematic experiences of students and their attitudes to using social support resources, for identifying the characteristics of students’ assessments of the conditions of higher education, their satisfaction and involvement in student life and attitudes towards inclusive education. The received results of monitoring were processed by means of the following qualitative and quantitative methods of the analysis: the content analysis; the analysis of percentage with the use of the Pearson’s chi-squared test (χ2); comparative analysis with the use of Student’s t-test; the median test and one-factorial dispersive analysis; correlation and factorial types of the analysis. The statistical software packages Statistica 7.0 were employed for the calculation of the results.Results and scientific novelty. The authors clarified the patterns of formation of the barrier-free socio-psychological environment of the university, which implements the concept of inclusive education. It was established that there are no global differences in the parameters of socio-psychological well-being between students with disabilities and students without disabilities. This determines the favourable social and psychological prerequisites for development of inclusive higher education. Belonging to the same socio-typological and age group and the same leading activity cause the similar experience (e.g. similar problems and difficulties) of both groups of students. The type of disabling health condition, i.e. a disabled student with the defined particular nosological group determines only the specifics of the difficulties, which might be faced in higher school. The conclusion was drawn that successful inclusion of students with disabilities in educational process and social space of university contributes to positive students’ perception of the high school environment.Practical significance. The research outcomes might be used to define the content, directions and forms of work to support students in the conditions of inclusive education. Thus, it is recommended to further develop the system of inclusive education through the following actions: to optimise social conditions of disabled students; to hold rehabilitational and psychological training sessions focused on communication; to organise educational work in order to raise students’ awareness of special technical means of inclusive education; to involve inner circle of people (parents, friends, fellow students) close to disabled students in the process of socio-psychological support.